An exploratory study of a low-level shared awareness measure using mission-critical locations during an emergency exercise. (September 2015) - Prytz, Erik; Rybing, Jonas; Jonson, Carl-Oscar; Petterson, Albin; Berggren, Peter; Johansson, Björn
A shared awareness of other teams' roles and tasks has been linked to successful performance in joint ventures. However, emergency management organizations responding to incidents do not always share critical information necessary for maintaining shared awareness. An instrument called Shared Priorities has previously been applied to measure aspects of shared situation awareness at level 2 and 3 in Endsley's (1995) model. This paper reports on a shared awareness instrument focused on level 1 situation awareness and its associated level of team shared awareness. Participants in a large emergency response exercise were asked to locate and rank geographical locations based on importance for overall mission success. The results show that organizations tended to rank locations relevant for their own work higher than positions relevant to other organization's tasks. The different organizations displayed different levels of inter-rater agreement within themselves concerning the ranking of these positions.